2004
DOI: 10.1002/biof.552210129
|View full text |Cite
|
Sign up to set email alerts
|

Development of the method for evaluating protective effect of food factors on THP‐1‐induced damage to human intestinal Caco‐2 monolayers

Abstract: Immune cells located in the intestinal epithelium interact with intestinal epithelial cells via soluble factors. In this study, a new in vitro model using a coculture system was constructed to analyze the interaction between intestinal epithelial cells and macrophage-like cells. Human intestinal epithelial Caco-2 cells were differentiated on semipermeable membranes. Human monocytic THP-1 cells were differentiated to macrophage-like cells and then cocultured on the basolateral side of the Caco-2 cell monolayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 3 publications
(3 reference statements)
1
22
0
Order By: Relevance
“…We have previously reported the interaction between Caco-2 cells as a model of human intestinal epithelial cells and PC12 cells as a model of neuronal cells [24,25]. We have also reported preliminary results on the interaction between intestinal epithelial cells and immune cells [26].…”
Section: Introductionmentioning
confidence: 81%
“…We have previously reported the interaction between Caco-2 cells as a model of human intestinal epithelial cells and PC12 cells as a model of neuronal cells [24,25]. We have also reported preliminary results on the interaction between intestinal epithelial cells and immune cells [26].…”
Section: Introductionmentioning
confidence: 81%
“…Both of these genes are important players in inflammatory intestinal diseases and their activation induces secretion of prostaglandin and the IL1β inflammatory cytokine by THP-1 cells, soluble factors that modulate interactions between epithelial and immune cells. To further analyze the relationship between THP-1 and intestinal cells, we utilized a co-culture model of intestinal inflammation (27). After co-culturing LPS-stimulated THP-1 cells with intestinal Caco2 cells, we observed an increase in proliferation of the intestinal cells (Figure 4B) that was diminished if Carlr was previously silenced in THP-1 cells (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Although not mimicking the ageing gut epithelium, FHs 74 Int and Caco-2 cell lines are employed world wide as suitable cell culture models displaying enterocyte like differentiation for studying the proliferation and gut integrity/permeability and immunomodulation at cellular level [ 23 - 30 , 32 , 33 ]. We first determined a concentration range of Enprocal, which was not cytotoxic (kill/disrupt) to the Caco-2 cell monolayers, needed to test the downstream intestinal permeability assays, adhesion assays etc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently an in vitro coculture system has been reported that could be utilized for an assay to search for drugs or food substances, which could prevent intestinal inflammation [ 33 ]. To study the cell-to-cell interaction between intestinal epithelial cells (Caco-2) and activated macrophages (THP-1), we utilized the similar Transwell model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation